Digital Video Watermarking Techniques: A Review (International Journal of Engineering and Computer Science, 2017)
Now a days internet becomes the most popular for exchange data & information over worldwide. These data & information are available on the internet in the form of digital media. In the era of internet authentication, protection and illegitimate redistribution of digital multimedia has become an essential issue. Digital Watermarking can be used to secure these illegal redistribution and reallocation. Digital Watermarking was invented against illegal work, owners’ authentication and security. Digital Video Watermarking is method to hiding some kind of data like audio, image, text into digital video sequences which is nothing but orders of successive still images. In this paper, we discuss about digital video watermarking techniques, robustness and also present the application where the uses of watermarking techniques and for better performance of video watermarking. We survey on properties of video watermarking, classification of video marking techniques, application and watermark attacks.